5
$\begingroup$

Can anyone help me to compute these integrals?

\begin{equation} \int_0^t\frac{1}{x}\exp\left(-\frac{a^2}{x}\right) \operatorname{erf}\left(\frac{b}{\sqrt{x}}\right)\,dx \end{equation}

here $\operatorname{erf}(\cdot)$ is error function.

I have already tried to take this integral by a lot of means, but I have not succeeded...

There is one more (it is consequence of the first one): \begin{equation} \int_0^b\frac{1}{\sqrt{a^2 + x^2}} \operatorname{erfc}\left(\sqrt{\frac{a^2 + x^2}{t}}\right)\,dx \end{equation}

Here $\operatorname{erfc}(\cdot)$ is complementary error function. Of course, I understand, that it is impossible to take them in elementary functions... But even with special functions I can't understand how to do it... Thanks in advance!

$\endgroup$
  • $\begingroup$ A small passing comment: If you had $1/x^{3/2}$ instead of $1/x$, you'd have an integral roughly of the form $\int \frac{d}{dx} [F(\frac{1}{\sqrt{x}})]^2 dx$, where $F$ is the error function. (Just set $a=b=1$ for convenience.) $\endgroup$ – abnry Jun 24 '13 at 16:49
5
$\begingroup$

Sometimes just using the integral form of error function can save you.

$\int_0^t\dfrac{1}{x}e^{-\frac{a^2}{x}} \text{erf}\biggl(\dfrac{b}{\sqrt{x}}\biggr)~dx$

$=\dfrac{2}{\sqrt{\pi}}\int_0^t\dfrac{1}{x}e^{-\frac{a^2}{x}}\int_0^\frac{b}{\sqrt{x}}e^{-u^2}~du~dx$

$=\dfrac{2}{\sqrt{\pi}}\int_0^t\dfrac{1}{x}e^{-\frac{a^2}{x}}\int_0^1e^{-\left(\frac{bu}{\sqrt{x}}\right)^2}~d\biggl(\dfrac{bu}{\sqrt{x}}\biggr)~dx$

$=\dfrac{2}{\sqrt{\pi}}\int_0^t\dfrac{1}{x}e^{-\frac{a^2}{x}}\int_0^1\dfrac{b}{\sqrt{x}}e^{-\frac{b^2u^2}{x}}~du~dx$

$=\dfrac{2b}{\sqrt{\pi}}\int_0^t\int_0^1\dfrac{e^{-\frac{b^2u^2+a^2}{x}}}{x\sqrt{x}}du~dx$

$=\dfrac{2b}{\sqrt{\pi}}\int_0^1\int_0^t\dfrac{e^{-\frac{b^2u^2+a^2}{x}}}{x\sqrt{x}}dx~du$

$=\dfrac{4b}{\sqrt{\pi}}\int_0^1\int_0^t-e^{-\frac{b^2u^2+a^2}{x}}~d\biggl(\dfrac{1}{\sqrt{x}}\biggr)~du$

$=\dfrac{4b}{\sqrt{\pi}}\int_0^1\int_\infty^\frac{1}{\sqrt{t}}-e^{-(b^2u^2+a^2)x^2}~dx~du$

$=\dfrac{4b}{\sqrt{\pi}}\int_0^1\int_\frac{1}{\sqrt{t}}^\infty e^{-(b^2u^2+a^2)x^2}~dx~du$

$=\dfrac{4b}{\sqrt{\pi}}\int_0^1\int_0^\infty e^{-(b^2u^2+a^2)x^2}~dx~du-\dfrac{4b}{\sqrt{\pi}}\int_0^1\int_0^\frac{1}{\sqrt{t}}e^{-(b^2u^2+a^2)x^2}~dx~du$

$=2b\int_0^1\dfrac{1}{\sqrt{b^2u^2+a^2}}du-\dfrac{4b}{\sqrt{\pi}}\int_0^1\biggl[\sum\limits_{n=0}^\infty\dfrac{(-1)^n(b^2u^2+a^2)^nx^{2n+1}}{n!(2n+1)}\biggr]_0^\frac{1}{\sqrt{t}}~du$

$=2b\int_0^1\dfrac{1}{\sqrt{b^2u^2+a^2}}du-\dfrac{4b}{\sqrt{\pi}}\int_0^1\sum\limits_{n=0}^\infty\dfrac{(-1)^n(b^2u^2+a^2)^n}{t^{n+\frac{1}{2}}n!(2n+1)}du$

$=2b\int_0^1\dfrac{1}{\sqrt{b^2u^2+a^2}}du-\dfrac{4b}{\sqrt{\pi}}\int_0^1\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{(-1)^nC_k^na^{2n-2k}b^{2k}u^{2k}}{t^{n+\frac{1}{2}}n!(2n+1)}du$

$=2b\biggl[\dfrac{\ln\left(b^2u+b\sqrt{b^2u^2+a^2}\right)}{b}\biggr]_0^1-\dfrac{4b}{\sqrt{\pi}}\biggl[\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{(-1)^na^{2n-2k}b^{2k}u^{2k+1}}{t^{n+\frac{1}{2}}k!(n-k)!(2n+1)(2k+1)}\biggr]_0^1$

$=2\ln\left(b^2+b\sqrt{a^2+b^2}\right)-2\ln(|a|b)-\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{(-1)^n4a^{2n-2k}b^{2k+1}}{\sqrt{\pi}t^{n+\frac{1}{2}}k!(n-k)!(2n+1)(2k+1)}$

$\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}\text{erfc}\left(\sqrt{\dfrac{a^2+x^2}{t}}\right)~dx$

$=\dfrac{2}{\sqrt{\pi}}\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}\int_\sqrt{\frac{a^2+x^2}{t}}^\infty e^{-u^2}~du~dx$

$=\dfrac{2}{\sqrt{\pi}}\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}\int_0^\infty e^{-u^2}~du~dx-\dfrac{2}{\sqrt{\pi}}\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}\int_0^\sqrt{\frac{a^2+x^2}{t}}e^{-u^2}~du~dx$

$=\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}dx-\dfrac{2}{\sqrt{\pi}}\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}\biggl[\sum\limits_{n=0}^\infty\dfrac{(-1)^nu^{2n+1}}{n!(2n+1)}\biggr]_0^\sqrt{\frac{a^2+x^2}{t}}~dx$

$=\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}dx-\dfrac{2}{\sqrt{\pi}}\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}\sum\limits_{n=0}^\infty\dfrac{(-1)^n(a^2+x^2)^{n+\frac{1}{2}}}{t^{n+\frac{1}{2}}n!(2n+1)}dx$

$=\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}dx-\dfrac{2}{\sqrt{\pi}}\int_0^b\sum\limits_{n=0}^\infty\dfrac{(-1)^n(a^2+x^2)^n}{t^{n+\frac{1}{2}}n!(2n+1)}dx$

$=\int_0^b\dfrac{1}{\sqrt{a^2+x^2}}dx-\dfrac{2}{\sqrt{\pi}}\int_0^b\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{(-1)^nC_k^na^{2n-2k}x^{2k}}{t^{n+\frac{1}{2}}n!(2n+1)}dx$

$=\left[\ln\left(x+\sqrt{a^2+x^2}\right)\right]_0^b-\dfrac{2}{\sqrt{\pi}}\biggl[\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{(-1)^na^{2n-2k}x^{2k+1}}{t^{n+\frac{1}{2}}k!(n-k)!(2n+1)(2k+1)}\biggr]_0^b$

$=\ln\left(b+\sqrt{a^2+b^2}\right)-\ln|a|-\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{(-1)^n2a^{2n-2k}b^{2k+1}}{\sqrt{\pi}t^{n+\frac{1}{2}}k!(n-k)!(2n+1)(2k+1)}$

$\endgroup$
  • $\begingroup$ You have done a really great work! But, I almost sure, that this approach is equivalent to series expansion of error function in initial integrand. $\endgroup$ – mechanician Jul 16 '13 at 9:36
  • $\begingroup$ And now I wonder if series in final expression is some special function... $\endgroup$ – mechanician Jul 16 '13 at 9:39
  • 1
    $\begingroup$ This is the most extravagant use of LaTex I've seen in a post... $\endgroup$ – jameselmore Jul 19 '13 at 13:12
0
$\begingroup$

\begin{eqnarray} \int\limits_0^t \frac{1}{x} \exp\left( -\frac{a^2}{x} \right) Erf\left( \frac{b}{\sqrt{x}}\right) dx=\\ 4 \int\limits_0^b \Phi^>(\sqrt{\frac{2}{t}} \sqrt{a^2+x^2}) \frac{1}{\sqrt{a^2+x^2}} dx=\\ 4 \int\limits_0^{arcsinh(b/a)} \Phi^>(\sqrt{\frac{2}{t}a \cosh(x)}) dx=\\ 4 arcsinh(\frac{b}{a}) - 4 \int\limits_0^{arcsinh(\frac{b}{a})} \Phi^<(\sqrt{\frac{2}{t}a \cosh(x)}) dx=\\ 2 arcsinh(\frac{b}{a}) - 4\left(\frac{1}{\sqrt{2 \pi}} \sum\limits_{n=1}^\infty (-\frac{1}{2})^{n-1} \frac{1}{(n-1)! (2n-1)} (\frac{2 a}{t})^{n-1/2} \int\limits_0^{arcsinh(\frac{b}{a})} [\cosh(x)]^{2n-1} dx\right) \end{eqnarray} In the first line we differentiated the integral with respect to $b$ then carried out the resulting integral by substituting for $1/\sqrt{x}$ and then integrated back again. In the second line we substituted $x\leftarrow a \sinh(x)$ and in the final line we expanded the CDF in a Taylor series . In order to finish the calculation it amounts to use the following result: \begin{equation} \int [\cosh(x)]^n dx = \frac{1}{2^{n-1}} \sum\limits_{p=0}^{2n-1} \binom{2n-1}{p} \frac{1}{2n-1-2 p} \sinh((2n-1-2 p) x) \end{equation}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.